Peningkatan Hasil Belajar Lay Up Shoot Melalui Penerapan Variasi Pembelajaran Siswa SMA Darul Ilmi Murni Medan - Sabaruddin Yunis Bangun; Brian Devani S (Journal Physical Education, Health and Recreation, 2017)
This study aims to determine the improvement of learning results of lay up shoot basketball through the application of variation of learning in students of class XI SMA Darul Ilmi Murni Medan in 2017. The research method used is descriptive, type of classroom action research with quantitative approach. To obtain the data in this study, then tested the results of learning before using the application of variation of learning (pre-test). The result of this study is from the implementation of learning using variation of learning and obtained the result of learning test using the variation of learning in cycle I obtained 22 students (68.75%) who have reached the level of mastery learning, while 10 students (31.25%) has not reached the level of mastery study, then the average score of 71.35. Then it was done again by teaching style with variation of learning from second result test result in cycle II obtained by 30 students (93,75%) reaching completeness level of learning, while 2 students (6,25%) have not reached learning mastery level, average student outcome is 80.20. Based on the results of data analysis can be assumed that through the variation of learning can improve the results of learning lay up shoot basketball in the class XI students Darul Ilmi Medan.